2013
DOI: 10.1111/jpy.12026
|View full text |Cite
|
Sign up to set email alerts
|

Protists in Arctic drift and land‐fast sea ice

Abstract: Global climate change is having profound impacts on polar ice with changes in the duration and extent of both land-fast ice and drift ice, which is part of the polar ice pack. Sea ice is a distinct habitat and the morphologically identifiable sympagic community living within sea ice can be readily distinguished from pelagic species. Sympagic metazoa and diatoms have been studied extensively since they can be identified using microscopy techniques. However, non-diatom eukaryotic cells living in ice have receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 84 publications
11
67
0
Order By: Relevance
“…Picoeukaryotes are among the least known protistan groups in the sea ice. The first studies on the diversity of sea-ice protists (not only picoeukaryotes) have shown sea-ice communities to consist of various phylotypes (Eddie et al, 2010;Bachy et al, 2011;Majaneva et al, 2012;Comeau et al, 2013). Our study complements these recent results with the first report on the quantitative distribution of particular groups of picoeukaryotes in first-year sea ice, including percentage of cells actively feeding by phagocytosis.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Picoeukaryotes are among the least known protistan groups in the sea ice. The first studies on the diversity of sea-ice protists (not only picoeukaryotes) have shown sea-ice communities to consist of various phylotypes (Eddie et al, 2010;Bachy et al, 2011;Majaneva et al, 2012;Comeau et al, 2013). Our study complements these recent results with the first report on the quantitative distribution of particular groups of picoeukaryotes in first-year sea ice, including percentage of cells actively feeding by phagocytosis.…”
Section: Discussionsupporting
confidence: 78%
“…Cryptophytes were the second most numerous group (Figure 4). Cryptophyte phylotypes related to Teleaulax and Hemiselmis were found in first-year sea ice in the Canadian Beaufort Sea (Comeau et al, 2013) and the Baltic Sea (Majaneva et al, 2012), but not in multiyear ice close to the North Pole (Bachy et al, 2011). Sequences of cryptophytes have been recovered from size-fractionated (0.2-3 mm) Arctic waters (Terrado et al, 2011).…”
Section: Importance Of Picoeukaryotes In Sea Icementioning
confidence: 97%
See 2 more Smart Citations
“…Increased impact of algal viruses and parasites would decrease the amount of food available for pelagic and benthic grazers. How these processes affect current blooms in the Arctic Ocean remains largely unknown, but both viruses and parasitic Syndiniales have been reported from sea ice (Wells & Deming 2006;Bachy et al 2011;Collins & Deming 2011;Comeau et al 2013;Piwosz et al 2013) and the water column (HowardJones et al 2002;Lovejoy et al 2006;Bachy et al 2011;Comeau et al 2011;Payet & Suttle 2013).…”
Section: Microbial Processesmentioning
confidence: 99%